2022
DOI: 10.1021/acsaem.1c03660
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin SnO2 Buffer Layer Aids in Interface and Band Engineering for Sb2(S,Se)3 Solar Cells with over 8% Efficiency

Abstract: The environmentally friendly antimony selenosulfide (Sb2(S,Se)3) semiconductor emerges as a promising light harvester for thin-film photovoltaics owing to its excellent material and optoelectronic properties. The alloyed Sb2(S,Se)3 is endowed with the complementary benefits of Sb2S3 and Sb2Se3, such as a tunable band gap within the range of 1.10–1.70 eV. In Sb2(S,Se)3 solar cells, the n-type semiconductor CdS is extensively used as an electron transport layer (ETL), which plays a role in extracting photogenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
0
24
0
Order By: Relevance
“…In our previous work, we constructed a single‐layer SnO 2 ‐based device of FTO/SnO 2 /Sb 2 (S,Se) 3 /spiro‐OMeTAD/Au, and found that the corresponding device exhibited a quite low efficiency of 0.92% that lagged far behind the current efficiency record of Sb 2 (S,Se) 3 solar cells. [ 21 ] This fact is closely associated with the poor quality of Sb 2 (S,Se) 3 films deposited onto the SnO 2 layer via the hydrothermal method. In contrast, the CdS substrates allow the fabrication of compact and uniform Sb 2 (S,Se) 3 absorber layer, which might be benefitted from the low lattice‐mismatch between CdS and Sb 2 (S,Se) 3 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous work, we constructed a single‐layer SnO 2 ‐based device of FTO/SnO 2 /Sb 2 (S,Se) 3 /spiro‐OMeTAD/Au, and found that the corresponding device exhibited a quite low efficiency of 0.92% that lagged far behind the current efficiency record of Sb 2 (S,Se) 3 solar cells. [ 21 ] This fact is closely associated with the poor quality of Sb 2 (S,Se) 3 films deposited onto the SnO 2 layer via the hydrothermal method. In contrast, the CdS substrates allow the fabrication of compact and uniform Sb 2 (S,Se) 3 absorber layer, which might be benefitted from the low lattice‐mismatch between CdS and Sb 2 (S,Se) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…A too‐thin layer would result in increased leakage current while a too‐thick layer would reduce the transmittance and increase the charge transfer resistance; both cases will affect the heterojunction quality, hindering the extraction and transport of electrons and thereby reducing the device performance. [ 21,30 ] In this work, we fabricated the SnO 2 ETL by spin‐coating commercial SnO 2 hydrosol (SH) precursor diluted by deionized water (DI), and the film thickness can be tuned by changing the spinning speed, the precursor concentration, and the number of spin‐coating. First, we optimized the volume ratio of SH/DW to obtain a reasonable thickness of ETL for high‐performance Sb 2 (S,Se) 3 solar cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations